(untitled) (Research, Society and Development, 2021)
Homogeneous forest plantations are commonly attacked by biotic agents due to their lower biological diversity. This type of planting, especially of eucalyptus, was intensified in Southeast of the state of Pará, Brazil, from the 1990s onwards. Thus, the objective of this study was to prospect the diversity of aerial entomofauna, evaluate their responses to seasonality, and detect the occurrence of possible important pest insects for monocultures of Eucalyptus spp. Yellow adhesive traps were used for sampling in plantations of E. urophylla and the hybrid E. grandis x E. urophylla. In total, 12 collections were carried out, with 27 traps each, divided into dry and rainy seasons, during two years in three municipalities in the Southeast of Pará. The Shannon-Wiener and Pielou diversity indices were calculated. Families were classified according to their faunal diversity, through the dominance, frequency, abundance, and constancy indices. The 2 x 2 factorial analysis test was performed to compare the effect of seasonality between the eucalyptus. A total of 10,280 individuals were collected, distributed in eight orders and 68 families. The most abundant orders were Hemiptera, Coleoptera, and Diptera, where Hemiptera was the most abundant in the dry season, and Diptera in the rainy season. The Aphalaridae and Thaumastocoridae families were the most important. The occurrence of the pest species Blastopsylla occidentalis, Glycaspis brimblecombei, and Thaumastocoris peregrinus was also recorded.